Peers as OSCE assessors for junior medical students: a review of routine use$da mixed methods study - Schwill, Simon; Fahrbach-Veeser, Johanna; Möltner, Andreas; Eicher, Christiane; Kurczyk, Sonia; Pfisterer, David; Szecsenyi, Joachim; Loukanova, Svetla (BMC medical education, 2020)
Peer-assisted learning is well established in medical education; however, peer tutors rarely act as assessors for the OSCE. In the compulsory, near-peer teaching programme covering basic medical skills at the University of Heidelberg, peer tutors serve as assessors on a formative OSCE. This study aimed to investigate the feasibility and acceptance of peer assessors and to survey the perceived advantages and disadvantages of their use.